Effectiveness and Efficiency of Farkiyah Box as Teaching Aids in Learning Fiqh al-Janā’iz - Harfiani, Rizka; Mavianti; Setiawan, Hasrian Rudi (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to evaluate the effectiveness and efficiency of Farkiyah Box as a teaching aid in improving students' understanding of the Fiqh al-Janā'iz material. This material requires a practical and applicable learning approach so that students not only understand the theory but are also able to implement it in real socio-religious life. The limitations of this study are that it only focuses on the evaluation aspect on a limited scale in one particular school, using a pre-experimental method that does not involve a control group. This study uses a quantitative approach of the pre-experimental type with a one-group pretest-posttest design and a response questionnaire. The subjects of this study were 36 ninth-grade students of SMP IT Baiti Jannati, Sunggal, Deli Serdang, North Sumatra. The subjects were selected using a purposive sampling technique. Data collection techniques used pretest-posttest, response questionnaires, and interviews. The data analysis technique used the n-gain value to measure effectiveness and the average questionnaire score for efficiency. The results of the study showed that the use of Farkiyah Box had an n-gain value of 0.742 on a scale of 0-1 which is in the high category, indicating a significant increase in student understanding. Meanwhile, the results of the response questionnaire showed an average score of 3.346 on a scale of 1-4 which indicated that this teaching aid was efficient and positively received by students. Thus, it can be concluded that Farkiyah Box has proven to be an effective and efficient teaching aid in learning Fiqh al-Janā'iz. It is worthy of being developed and applied more widely in Islamic educational institutions. This study recommends Farqiyah Box as a new prototype teaching aid model for teaching Fiqh al-Janā'iz.